Spatial and Temporal Variation in the Acoustic Habitat of Bottlenose Dolphins (Tursiops aduncus) within a Highly Urbanized Estuary - Marley, Sarah A.; Erbe, Christine; Salgado Kent, Chandra P.; Parsons, Miles J. G.; Parnum, Iain M. (Frontiers in Marine Science, 2017)
There is growing awareness of underwater noise in a variety of marine habitats, and how such noise may adversely aﬀect marine species. This is of particular concern for acoustically-specialised species, such as dolphins. In order to ascertain the potential impacts of anthropogenic noise on these animals, baseline information is required for deﬁning the soundscape of dolphin habitats. The Swan-Canning River system in Western Australia ﬂows through the city of Perth, and experiences numerous anthropogenic activities. Despite this, the river system is home to a community of Indo-Paciﬁc bottlenose dolphins (Tursiops aduncus). To provide a baseline soundscape description of dolphin habitat, over 11,600 h of acoustic data were analysed from ﬁve sites within the Swan River (from Fremantle Inner Harbour to 20 km upstream) across an eight-year period. Multiple sound sources were recorded at these sites, including: snapping shrimp; ﬁshes; dolphins; pile-driving; bridge and road traffic; and vessel traffic. The two most prevalent sound sources, vessel traffic and snapping shrimp, likely have very diﬀerent eﬀects on dolphin communication with the former expected to be more disruptive. Sites were characteristic in their prominent sound sources, showing clear among-site variations, with some sites being ‘noisier’ than others based on broadband noise levels, octave-band noise levels, and power spectrum density percentiles. Perth Waters had the highest broadband noise (10 Hz – 11 kHz; mean 113 dB re 1 µPa rms), whilst Heirisson Island was quietest (mean 105 dB re 1 µPa rms). Generalised estimating equations identiﬁed variation in broadband noise levels within sites at a ﬁne temporal scale, although sites diﬀered in the signiﬁcance of temporal variables. At Mosman Bay, a long-term dataset spanning eight years highlighted inter-annual variation in broadband noise levels, but no overall upwards or downwards trend over time. Acoustic habitats of the Swan River displayed signiﬁcant variations at a variety of temporal and spatial scales, throughout areas frequented by the local dolphin community. Such variations should be quantiﬁed when assessing dolphin acoustic habitat as they may provide signiﬁcant clues to dolphin behaviour.